Treatment of Venous Thromboembolism with Edoxaban over 18 Months: Results from ETNA-VTE Europe - Agnelli, Giancarlo; Hoffmann, Ulrich; Hainaut, Philippe; Gaine, Sean; Ay, Cihan; Coppens, Michiel; Schindewolf, Marc; Jimenez, David; Fronk, Eva-Maria; Souza, José; Laeis, Petra; Bramlage, Peter; Brüggenjürgen, Bernd; Levy, Pierre; Cohen, Alexander T.; on behalf of the ETNA-VTE-Europe investigators (Thrombosis and Haemostasis, 2025)
The benefits and risks of extending anticoagulant treatment beyond the first 3 to 6 months in patients with venous thromboembolism (VTE) in clinical practice are not well understood.ETNA-VTE Europe is a prospective, noninterventional, post-authorization study in unselected patients with VTE treated with edoxaban in eight European countries for up to 18 months. Recurrent VTE, major bleeding, and all-cause death were the primary study outcomes.The median age of the 2,644 patients was 65 years; 46.6% were female, and 22.8% had a history of VTE. The median treatment duration was 50.6 weeks (interquartile range: 23.4–77.7). VTE recurrence occurred in 100 patients (3.8% at an annual rate of 2.7%/year); 37 patients (1.4%) were on edoxaban at the time of the event, with a corresponding annualized rate of 1.6%/year. Major bleeding was experienced by 37 patients (1.4%) during edoxaban treatment, corresponding to an annualized rate of 1.5%/year. Overall, 95 patients died (3.6%; annualized rate 2.6%/year), with the majority for reasons other than VTE- and cardiovascular (CV)-related causes. Out of 15 deaths (1.9%; annualized rate 2.1%/year) that occurred during edoxaban treatment, 1 was related to VTE and 11 related to CV (annualized rate 0.0%/year and 0.5%/year).ETNA-VTE Europe provides evidence for the real-world effectiveness of edoxaban treatment (up to 18 months) based on a low rate of VTE recurrence, all-cause death, and major bleeding, and is aligned with the results of the randomized clinical trial reassuring the use of edoxaban in the treatment of VTE in routine clinical practice.
Keywords: venous thromboembolism; pulmonary embolism; edoxaban; clinical outcomes; safety